Lung Clear “Sugar” Cell Tumor and Jak V617f Positive Essential Thrombocythemia: A simple Coıncıdence? - Volkan Yazak; Gokhan Sargin; Irfan Yavasoglu; Gurhan Kadikoylu; Canten Tataroglu; Gokay Bozkurt; Zahit Bolaman (Mediterranean Journal of Hematology and Infectious Diseases)
The primary clear cell tumor of the lung is an extremely rare benign tumor, which is called “sugar tumor”, because of the large content of glycogen. Here we are presenting essential thrombocythemia and lung clear cell tumor which was not reported before to the best of our knowledge.